2019
DOI: 10.18488/journal.aefr.2019.97.743.751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Board Diversity on Financial Performance of the Vietnamese Listed Firms

Abstract: This study investigated the impact of board diversity on the financial performance of listed firms on the Vietnamese stock exchange. Four demographic characteristics of board members (gender, nationality, level of education and level of age) were used as the proxies for diversity. The data were analyzed by different methods including Pooled OLS regression, Fixed Effect Model (FEM), Random Effect Model (REM) and Generalized Method of Moments (GMM) using a sample of 482 companies listed in the period from 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
5
9
1
Order By: Relevance
“…The possible explanation for this is that females on board are mostly voluntarily assuring compliance with stated rules and regulations that govern the operation of the firms. This is in line with the works of Bin Khidmat et al (2020), Guping et al (2020), Haque and John (2020), Ngo et al (2019).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The possible explanation for this is that females on board are mostly voluntarily assuring compliance with stated rules and regulations that govern the operation of the firms. This is in line with the works of Bin Khidmat et al (2020), Guping et al (2020), Haque and John (2020), Ngo et al (2019).…”
Section: Resultssupporting
confidence: 90%
“…operation of the firms. This is in line with the works of Bin Khidmat et al (2020),Guping et al (2020),Haque and John (2020),Ngo et al (2019).…”
supporting
confidence: 92%
“…The improvement in the performance of enterprises when the percentage of women's participation is high in the BOD is also consistent with the announcement of Jurkus et al (2011), Ain et al (2021) in developed countries such as China or America. Moreover, the positive correlation between gender diversity in the BOD and firm performance has also been confirmed by authors in developing countries (Mohsni et al, 2021) such as Vietnam (Ngo et al, 2019), Bangladesh (Rashid, 2015), India (Duppati et al, 2020) when they provide evidence about the positive impact of gender diversity boards and firm performance.…”
Section: Empirical Results and Analysissupporting
confidence: 55%
“…Moreover, a study conducted by Srivastava (2018) in India found that the presence of female directors on the board has a negative association with the COE and has a positive impact on the firm performance. Different studies conducted in different parts for the world studying the impact of gender diversity on firm performance like Ngo et al (2019), in Vietnam, Aggarwal et al (2019) in India and Khan and Abdul Subhan (2019) on PSE 100 index in Pakistan all found that gender diversity enhances firm performance. However, in a study conducted in Malaysia by Razali (2018) found that female directors on the board decrease the firm performance.…”
Section: Board Characteristics 221 Board Independence (Ined)mentioning
confidence: 99%